Sub‐second variability in black‐hole X‐ray binary jets. Issue 4 (29th April 2019) - Vincentelli, F. M.; Casella, P.
Abstract : In the last 10 years, multiwavelength fast variability studies of low‐mass X‐ray binaries have shown a dramatic development. A key discovery was the detection of O‐IR sub‐second fluctuations in two black‐hole transients, lagging the X‐rays by ≈0.1 s. This demonstrated how the fluctuations observed in the inflow could be transferred to the jet, allowing, therefore, also to study in a completely new way the physical processes that take place at the base of the jet. In this article, we review the latest developments of the study of jets with this new approach, focusing on the results obtained with cross‐spectral analysis techniques.